Digital social innovations in rural areas – process tracing and mapping critical junctures - Sommer, Carola Rebecca; Chilla, Tobias; Birnbaum, Lisa; Kröner, Stephan (Journal of Rural Studies, 2025)
In recent years, digitalisation projects have helped rural areas to bridge some of the urban-rural disparities, such as accessibility issues as well as the digital literacy divide. To further exploit the potential of digitalisation for rural areas, we aim to understand the implementation of digitalisation processes and their conceptual alignment with Digital Social Innovation (DSI). As an example of Neo-Endogenous Regional Development (NERD) approaches, this perspective provides rich insights into small-scale rural adaptation in a rapidly digitising world. DSI encompasses a strong process perspective, but lacks a broader empirical application. It is a multifaceted concept that includes bottom-up participation, learning and empowerment. To operationalise the process perspective within DSI, we apply a process tracing approach within a qualitative comparative analysis of four case studies. Based on schematic mappings, we conclude with four critical junctures that provide insights for rural DSI. First, innovation can be triggered both endogenously and exogenously, with different implications for path dependencies. Second, participatory processes are crucial for digital innovation in rural communities. Third, hybridisation as an intermediate step can help to reduce the digital divide. Finally, successful institutionalisation benefits from collaborative learning. These findings outline how successful digital social innovation generates impacts beyond the project scope.
CRIS-Team Scopus Importer:2024-12-06
Keywords: digital social innovation; embeddedness; Neo-endogenous regional development; Rural digitalisation; Social innovation

Place attachment and digitalisation in rural regions - Birnbaum, Lisa; Wilhelm, Carola Rebecca; Chilla, Tobias; Kröner, Stephan (Journal of Rural Studies, 2021)
This paper reflects on place attachment in times of digitalisation in rural regions. Our qualitative study explores the extent to which and with which characteristics place attachment ‘translates’ into the digital format. The paper analyses 193 digital projects presented in the internet. These cases cover several European countries with a particular focus on Germany. The analysis is based on a three-dimensional framework involving attachment concepts, space/place and digitalisation. From a systematic categorisation of the case studies, six result patterns emerge: Some of them confirm place attachment patterns, which are well known from the debate on ‘non-digital’ place attachment (e.g., the importance of emotions). Other findings show that digitalisation does make a difference, in particular concerning abstract, non-localised spatial references to the rural area. Finally, we deduce some implications from our findings for practical implementation in regional development.<br
Keywords: Place attachment; Regional identity; Digitalisation; Rural areas; Sense of place; Regional development

Short Value Chains in Food Production: The Role of Spatial Proximity for Economic and Land Use Dynamics - Bertram, Dominik; Chilla, Tobias; Wilhelm, Carola Rebecca (Land, 2021)
Agricultural land demand tends to be in weak condition vis-a-vis settlement development, transport infrastructure and industry expansion. At the same time, the awareness and demand of consumers for regional food is constantly rising, in particular in urban regions. The resulting challenge is that high demand for regional food is concentrated at places where land for food production tends to be particularly under pressure. Against this background, our article reflects on the extent to which regional food supply chains support the status of agricultural demand in the competition for land. The main aim of our paper is to understand the role of proximity between the different stages of value creation, including cultivation, production (manual or industrial) and trade (retail, direct marketing). Our empirical study on the example of three products in Bavaria (Germany) shows that short distances within food value chains support the agricultural condition in land use dynamics (beer, sweet cherry, asparagus). The analyses are based on official and internal statistics as well as expert interviewing. This mixed-methods approach results in value-creation mappings and provides spatial differentiation of the economic process. Proximity between at least two stages of value creation plays an important role to explain the economic trends and land use dynamic. These findings are rooted in arguments of efficiency, tacit knowledge, networks, as well as product reputation. However, the role of proximity does not automatically play a role but has to be stabilized by strategic measures such as product innovation and marketing measures.
CRIS-Team WoS Importer:2021-10-15

The regional dimension in GPN – Mapping value creation and governance of the Bavarian beer sector - Wilhelm, Carola Rebecca; Chilla, Tobias (Geoforum, 2023)
Contemporary crises have stimulated a new political and scientific interest in economic power structures and regionalisation. In particular, this concerns the local–global nexus, a key argument within the Global Production Networks (GPN) literature. This addresses the question of how global governance concepts help us understand regional production networks within multiscale production processes, mostly linked to transnational corporations. We contribute to this question with a focus on value creation and governance structures beyond, or ‘in the shade’ of, the often-prevailing dominance of transnational lead firms. Here, we present an analysis of value creation and governance in the Bavarian beer sector, building on comprehensive statistical data and expert interviews. The interpretation is based on a visual value creation mapping. We draw on three analytical dimensions from the GPN debate: corporate, institutional and collective power. The analysis shows that the local level can be a hub for multi-layered dynamics in value creation and governance. We find strong local lead firms, which succeed in linking global dynamics and protecting local networks. In this process of segmentation some local firms build a strong regional network that is economically rather independent from larger firms. Institutional governance plays an important role, and regional assets such as education facilities or cultivation contexts come into play. Our results indicate that the ‘local’ might be a stronger part of the local–global nexus than often assumed.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Beer; Global production networks; Governance; GPN; Regional value creation; Value capture